DEVELOPMENT AND USAGE OF THE ELECTRONIC VIDEO RESOURCES FOR EDUCATIONAL PURPOSES - Yaroslav M. Hlynsky; Dmytro V. Fedasiuk; Victoriia A. Riazhska (Information technologies and learning tools, 2017)
This article discusses the theoretical foundation, the creation and implementation of the electronic educational video resources (EEVR) in the example of the development and the usage of the collection of video tutorials in event-driven programming theme, which is studied in the framework of the subject "Informatics" by students of many specialties. It offers some development of the existing conceptual and categorical apparatus concerning EEVR development. It is alleged that the video tutorials allow you to automate the process of learning, redistribute instructional time for the benefit of students' independent work, to provide classroom release time for the teaching of the theoretical issues of the course that is aimed at improving the fundamental nature of training. Practical recommendations for the development of the effective EEVR, which may be useful for the authors of e-learning courses for students of different forms of training are proposed.